Art and Judaism in the Greco-Roman world: toward a new Jewish archaeology - Fine, Steven (Cambridge University Press, 2005)
Building an ancient synagogue on the Delaware: Philadelphia's Henry S. Frank Memorial Synagogue and constructions of Jewish art at the turn of the twentieth century -- The old-new land: "Jewish archaeology" and the Zionist narrative -- Archaeology and the search for "non-rabbinic Judaism" -- Art history: transmitting Jewish artlessness to new generations -- Toward a new "Jewish archaeology": methodological reflections -- Art and identity in latter Second Temple period Judaism: the Hasmonean royal tombs at Modi'in -- Art and identity in late antique Palestine: the Na'aran synagogue -- Art and identity in diaspora communities in late antiquity: from Nehardea to Rome -- Between Rome and Jerusalem: the date palm as a "Jewish symbol" -- "The lamps of Israel": the menorah as a Jewish symbol -- The Dura Europos synagogue and its liturgical parchment -- Synagogue mosaics and liturgy in the land of Israel -- Sanctity and the art of ancient synagogues.